The application of niobium compounds as catalysts in continuous flow reaction - Jin, Jing (2018)
This Thesis describes the application of niobium oxide and niobium phosphate as solid acids for conducting continuous flow reactions, such as the Friedel-Crafts Reaction and the Skraup Reaction, and also as supports for photosensitiser immobilisation. Chapter 1 introduces the concepts of green and sustainable chemistry, and give a review of niobium and niobium compounds, especially niobium oxide and niobium phosphate as well as their applications. A summary of flow chemistry is also presented. The continuous flow systems used to conduct the work of this Thesis are described in Chapter 2. Chapter 3 introduces continuous alkylation of aniline with dimethyl carbonate or methanol over niobium solid acids. The synthesis process is automated by a self-optimisation system to search the best conditions for different products, including the NH2 group methylation product monomethyl aniline and dimethyl aniline, and the Friedel-Crafts alkylation product N,N-dimethyl-p-toluidine. Chapter 4 describes the first exploration of the continuous Skraup synthesis of quinolones with heterogeneous catalyst niobium phosphate. A dissymmetrics substituted quinoline compound, 4-(quinolin-6-yl methyl)aniline, was synthesized, and its crystal was grown and the structure was determined by crystallographic analysis for the first time. Chapter 5 discussed the immobilisation of a photosensitiser meso-tetraphenylporphyrin on niobium solid acids, and the activity of these supported photocatalysts in continuous photo-oxidation, including the photo-oxidation of α-terpinene to ascaridole and the semi-synthesis of an antimalarial drug, artemisinin ART. Finally, Chapter 6 summarises the work described in this Thesis and examines the success of the techniques and approaches discussed. A summary of potential routes for further study is also presented.